Optimisasi Kecerdasan Emosional, Kecerdasan Spiritual dan Persepsi Kontrol Perilaku Terhadap Pengetahuan Etika dalam Penyusunan Laporan Keuangan Usaha, Mikro, Kecil dan Menengah (UMKM) di Desa Margasari - Silvi Anggraeni; Dedi Mulyadi; Yanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of optimizing emotional intelligence, spiritual intelligence, and perceived behavioral control on ethical knowledge in preparing MSME financial reports using a quantitative approach. The sample in this study was 109 MSMEs. The sampling technique uses purposive sampling technique. Data analysis uses SmartPLS, with the outer model stage containing the convergent validation test, discriminant validity test, reliability test, and the inner model which contains path coefficient significance testing, R2 coefficient of determination testing, Q2 relapse predictive testing, Goodness of Fit or GoF testing. The results of this research show that emotional intelligence has a significant effect on ethical knowledge in preparing MSME financial reports, while spiritual intelligence has no effect on ethical knowledge in preparing MSME financial reports, and perceived behavioral control has a significant effect on ethical knowledge in preparing MSME financial reports.